Development of a web‐based application and multicountry analysis framework for assessing interdicted infections and cost‐utility of screening donated blood for HIV, HCV and HBV. Issue 6 (8th June 2017) - Custer, B.; Janssen, M. P.; Hubben, G.; Vermeulen, M.; van Hulst, M.
Abstract : Background and Objectives: Most countries test donations for HIV, HCV and HBV using serology with or without nucleic acid testing (NAT). Cost‐utility analyses provide information on the relative value of different screening options. The aim of this project was to develop an open access risk assessment and cost‐utility analysis web‐tool for assessing HIV, HCV and HBV screening options (http://www.isbtweb.org/working-parties/transfusion-transmitted-infectious-diseases/ ). An analysis for six countries (Brazil, Ghana, the Netherlands, South Africa, Thailand and USA) was conducted. Materials and Methods: Four strategies; (1) antibody assays (Abs) for HIV and HCV + HBsAg, (2) antibody assays that include antigens for HIV and HCV (Combo) + HBsAg, (3) NAT in minipools of variable size (MP NAT) and (4) individual donation (ID) NAT can be evaluated using the tool. Country‐specific data on donors, donation testing results, recipient outcomes and costs are entered using the online interface. Results obtained include the number infections interdicted using each screening options, and the (incremental and average) cost‐utility of the options. Results: In each of the six countries evaluated, the use of antibody assays is cost effective or even cost saving. NAT has varying cost‐utility depending on the setting, and where adopted, the incremental cost‐utility exceeds any previously defined or proposed threshold in each country. Conclusion: The web‐tool allows an assessment of infectious units interdicted and value for money of different testing strategies. Regardless of gross national income (GNI) per capita, countries appear willing to dedicate healthcare resources to blood supply safety in excess of that for other sectors of health care.